PENGARUH PENERAPAN POLA PEMBERDAYAAN BERPIKIR MELALUI PERTANYAAN (PBMP) DENGAN MODEL PEMBELAJARAN THINK PAIR SHARE (TPS) TERHADAP AKTIVITAS BELAJAR, KEMAMPUAN BERPIKIR KRITIS DAN HASIL BELAJAR KOGNITIF MAHASISWA PADA MATA KULIAH EVALUASI PEMBELAJARAN - Agus Muliadi (Bioscientist : Jurnal Ilmiah Biologi, 2013)
This study aims to determine the effect of the application of Thinking Poverty through Question (PBMP) Model with Think Pair Share (TPS) model of learning activities, critical thinking skills, and cognitive learning outcomes of students in biology learning evaluation courses. The design used in this study was Pretest-Postest Nonequivalent Control Group Design and the resulting data were analyzed using covariance analysis (Anakova). Based on the research data, it is known that: 1) the application of PBMP with cooperative learning model of TPS is more effective to improve student learning activity compared to learning by lecturing; 2) there is a significant effect on the application of PBMP with the TPS learning model to students' critical thinking skills, since Fhitung is 41.18 and the significance of 0.000, smaller than alpha 0.05; and 3) there is a significant effect of PBMP implementation with cooperative learning model of TPS on cognitive learning outcomes, because Fcount is 384.09 and significance 0.000, smaller than alpha 0.05.